2007
DOI: 10.1073/pnas.0705947104
|View full text |Cite
|
Sign up to set email alerts
|

Disulfooxy fatty acids from the American bird grasshopper Schistocerca americana , elicitors of plant volatiles

Abstract: A previously unidentified class of compounds has been isolated from the regurgitant of the grasshopper species Schistocerca americana. These compounds (named here ''caeliferins'') are composed of saturated and monounsaturated sulfated ␣-hydroxy fatty acids in which the -carbon is functionalized with either a sulfated hydroxyl or a carboxyl conjugated to glycine via an amide bond. The regurgitant contains a series of these compounds with fatty acid chains of 15-20 carbons and in varying proportions. Of these, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
127
2
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(133 citation statements)
references
References 43 publications
1
127
2
3
Order By: Relevance
“…We have already reported glutamic acid and glutamine conjugates identified in crickets, larval fruit flies (10), and in katydids (9). In general, in most of the insects outside of Lepidoptera studied thus far, glutamic acid conjugates are dominant with only trace amounts of glutamine conjugates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have already reported glutamic acid and glutamine conjugates identified in crickets, larval fruit flies (10), and in katydids (9). In general, in most of the insects outside of Lepidoptera studied thus far, glutamic acid conjugates are dominant with only trace amounts of glutamine conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that this ingenious plant defense system is triggered by substances in the regurgitants of the herbivores. The best known of these plant volatile elicitors are the fatty acid amino acid conjugates (FACs) that first were identified from beet armyworm, Spodoptera exigua, larvae (3) but later also found in several other lepidopteran species (4)(5)(6)(7)(8) and other insects (9,10). Of the FACs, volicitin [N-(17-hydroxylinolenoyl)-L-glutamine], is the most active elicitor for seedlings of most cultivars of Zea mays (3,11,12).…”
mentioning
confidence: 99%
“…The elicitors in saliva are often species-specific and diverse in structure (35,36). They range from plant cell wall fragments (37,38), peptides derived from ingested plant proteins (39), to fatty acid-amino acid conjugates (16,40), sulfur-containing fatty acids (41), and enzymes (15,42). In regurgitant of Pieris caterpillars, the enzyme β-glucosidase has been identified as playing a major role in eliciting plant responses after herbivory, including volatile emission (15).…”
Section: Discussionmentioning
confidence: 99%
“…The chemical nature of a few elicitors of feeding-induced plant defense responses are known: fatty acid-amino acid conjugates, including volicitin, of several lepidopterans (6,7,(23)(24)(25)(26); peptides derived by proteolysis from chloroplastic ATP synthase of herbivore-damaged plants (27,28); disulfo-oxy fatty acids of grasshopper regurgitant, named caeliferins (29); and the enzyme ␤-glucosidase from Pieris brassicae oral secretions (8). Application of these elicitors onto plant wounds results in the release of volatiles that repel ovipositing herbivores (30) or attract natural enemies of herbivores (31).…”
Section: Discussionmentioning
confidence: 99%